Penguatan Kemandirian Manajemen Ekonomi Desa Melalui Pengembangan Unit Usaha Desa Uning Berbasis Ekonomi Digital - Ilhamdi Ilhamdi; Richasanty Septima S; Ira Zulfa (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2023)
Realizing rural economic independence is one of the national development goals and requires village potential, community social potential, and natural resource potential which are actors as well as objects in development. In addition, in realizing independence, it is necessary to optimize village business units. The Village Business Unit is an institution established by the village community that does not focus on profit or profit but must also be managed with social souls, or social entrepreneurship. However, the current reality shows that many villages do not know how to set up and optimize their own business units. As an effort to drive the local and regional economy, a strategy is needed to utilize and optimize the potential of local resources, be it natural resources, human resources or other economic resources. And the service method used is socialization and discussion. Based on the results of the tests before and after the implementation of the activities, it can be seen that there was an increase in understanding before and after the socialization, which means that the community has begun to understand what are the ways to strengthen the economic independence of their village business units.